2011
DOI: 10.1182/blood-2010-07-298422
|View full text |Cite
|
Sign up to set email alerts
|

Rational engineering of L-asparaginase reveals importance of dual activity for cancer cell toxicity

Abstract: Using proteins in a therapeutic context often requires engineering to modify functionality and enhance efficacy. We have previously reported that the therapeutic antileukemic protein macromolecule Escherichia coli L-asparaginase is degraded by leukemic lysosomal cysteine proteases. In the present study, we successfully engineered L-asparaginase to resist proteolytic cleavage and at the same time improve activity. We employed a novel combination of mutant sampling using a genetic algorithm in tandem with flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
1
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 34 publications
2
96
1
12
Order By: Relevance
“…In addition to Y176F, W66Y with both high glutaminase activity and higher cytotoxicity also appears to be an effective drug. Similar observations were reported by others for an EcA variant N24A mutation that showed stable glutaminase activity and also improved cell-killing properties (48).…”
Section: Discussionsupporting
confidence: 76%
“…In addition to Y176F, W66Y with both high glutaminase activity and higher cytotoxicity also appears to be an effective drug. Similar observations were reported by others for an EcA variant N24A mutation that showed stable glutaminase activity and also improved cell-killing properties (48).…”
Section: Discussionsupporting
confidence: 76%
“…As a result, the benefits compared with the use of native asparaginase are reduced. Several studies have shown that the structure of asparaginase permits the introduction of modifications without appreciable loss of enzymatic function (7,22,23). The data we present here may provide a rationale for the generation of novel modified versions of asparaginase.…”
Section: Discussionmentioning
confidence: 83%
“…According to Panosyan et al [16] the effective deamination of glutamine by L-asparaginase appears to contribute to the decrease of asparagine depletion by depriving the asparagine synthetase of glutamine, the precursor asparagine biosynthesis. Bacterial L-asparaginase, used in therapeutic protocols, has low glutaminase activity but toxicity reactions are attributed to this activity [17,18]. Herein L-glutaminase activity was not detected in crude enzyme (concentrated or not) produced by A. terreus (PC-1.7.A) even after 60 min of the reaction.…”
Section: Discussionmentioning
confidence: 94%